Nós, os ossos que aqui estamos, pelos vossos esperamos: a higiene e o fim dos sepultamentos eclesiásticos em São Luís (1828 – 1855) - Coe, Agostinho Júnior Holanda (2008)
Discussion about the extinction of church burials and the construction of new cemeteries in São Luís. In the nineteenth century, with the affirmation of medicine, the burials conducted within religious temples became the target of numerous interdictions. The development of “hygienism” gradually constructed the idea that burials within religious temples were harmful to health, since they exhaled miasmatic vapors which caused physical and even moral damages to the living. With the increase of epidemics in the nineteenth century in São Luís, the medical discourse, which claimed for the construction of new cemeteries far from the towns, water fountains, and where the wind blew reversely in relation with the urban environment, acquired further visibility. In 1828, the “Imperial Law of Municipalities Restructuring” became one among various essays of reorganization of São Luís urban space and of construction of new burial places, far away from churches, since the existing cemeteries, up to the middle of the nineteenth century, were basically for poor and helpless. In 1855, after various previous epidemical irruptions, the city was attacked by a big irruption of smallpox, which led the norm into practice, with the building of the Gavião Cemetery. Since then, that cemetery became a burial place not only for indigents and slaves, but also for a considerable part of the wealthier classes of São Luís.